2020
DOI: 10.21873/anticanres.14279
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Magnetic Resonance Imaging in the Pre-operative Evaluation of Women Diagnosed With Atypical Endometrial Hyperplasia

Abstract: Background/Aim: To evaluate the role of MRI in patients with atypical endometrial hyperplasia (AEH) and incorporate MRI findings in predictive models estimating the risk of co-existent endometrial cancer (EC). Patients and Methods: Data from 189 women diagnosed with AEH and had MRI scan prior to operation, over nine years, were retrospectively collected. Results: Histology showed EC in 51 (27%) cases. Presence of myometrial invasion on MRI was more commonly detected in patients with EC compared to those with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 14 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…The results of the scoping review were reported according to the Preferred Reporting Items for Systematic reviews and Meta-criteria and were included in our review. We included 24 primary studies, [9][10][11][13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] three meta-analyses, [17][18][19] and one poster presentation. 12 The characteristics of the 28 included studies are shown in Table 2.…”
Section: Stage 5: Summarizing Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the scoping review were reported according to the Preferred Reporting Items for Systematic reviews and Meta-criteria and were included in our review. We included 24 primary studies, [9][10][11][13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] three meta-analyses, [17][18][19] and one poster presentation. 12 The characteristics of the 28 included studies are shown in Table 2.…”
Section: Stage 5: Summarizing Resultsmentioning
confidence: 99%
“…12 The characteristics of the 28 included studies are shown in Table 2. Five studies were multicentric, 17-19, 27,35 five studies were from Turkey, 11,15,20,23,25 four studies were from the USA, 12,13,21,22 two studies were from the UK, 14,16 two studies were from Canada 10,34 and there was one study from each of Australia, 9 South Korea, 24 France, 26 Belgium, 28 Italy, 29 Denmark, 30 Greece, 31 Norway, 32 Taiwan, 33 and China. 36 These studies included the data of 7409 patients and recorded 2377 concurrent EC cases (32.1%).…”
Section: Stage 5: Summarizing Resultsmentioning
confidence: 99%
See 3 more Smart Citations